Correlation of intermolecular acyl transfer reactivity with noncovalent lattice interactions in molecular crystals: toward prediction of reactivity of organic molecules in the solid state - Krishnaswamy, Shobhana; Shashidhar, Mysore S. (Journal of Organic Chemistry, 2018)
Intermolecular acyl transfer reactivity in several molecular Acyl transfer reactivity can be predicted in solution based crystals was studied, and the outcome of the reactivity was analyzed in the light of structural information obtained from the crystals of the reactants. in solid state Minor changes in the molecular structure resulted in significant variations in the noncovalent interactions and packing of molecules in the crystal lattice, which drastically affected the facility of the intermolecular acyl transfer reactivity in these crystals. Analysis of the reactivity vs crystal structure data revealed dependence of the reactivity on electrophile ... nucleophile interactions and C-H center dot center dot center dot pi interactions between the reacting molecules. The presence of these noncovalent interactions augmented the acyl transfer reactivity, while their absence hindered the reactivity of the molecules in the crystal. The validity of these correlations allows the prediction of intermolecular acyl transfer reactivity in crystals and co-crystals of unknown reactivity. This crystal structure-reactivity correlation parallels the molecular structure-reactivity correlation in solution-state reactions, widely accepted as organic functional group transformations, and sets the stage for the development of a similar approach for reactions in the solid state.